2015
DOI: 10.1007/s00268-015-3069-6
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment in Selected Patients with Severe Critical Limb Ischemia

Abstract: Conservative management in our selected patients with CLI results in a moderate rate of wound closure and acceptable amputation rates albeit with a high mortality rate. For patients not eligible for endovascular revascularization or bypass surgery, conservative treatment could be a viable option besides primary limb amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Patients with limb ischemia are a fragile and vulnerable group of patients 12 whose outcomes are negatively affected if the usual standard of care is delayed. It is therefore important that during a future pandemic, regular medical care should continue for these patients, with caregivers being aware of these patients and referring in time for revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with limb ischemia are a fragile and vulnerable group of patients 12 whose outcomes are negatively affected if the usual standard of care is delayed. It is therefore important that during a future pandemic, regular medical care should continue for these patients, with caregivers being aware of these patients and referring in time for revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Although many reports about revascularization for patients with CLI have been published, there are still few detailed reports about conservative treatments. [4][5][6][7][8][9][10][11] In this study, the systemic problems of patients who received conservative treatment were ischemic heart disease, respiratory occlusive disease, and a bedridden status. Low cardiac function and respiratory dysfunction were the main contraindications for surgery under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the follow-up period for conservatively treated patients with CLI was one or two years. 4,10) Thomas, et al reported that the median time to mortality was seven months, and the two-year survival rate was 55% in patients with CLI who underwent conserva-tive treatment. 10) Gu, et al reported the one-year outcomes of 30 patients with CLI who received conservative treatment, including two patients with revascularization failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CLI have cardiovascular event rates higher than those in patients with symptomatic coronary artery disease 4. Thomas et al found that in patients with conservatively treated severe CLI, all-cause mortality was 58% with a 2-year survivability rate of 55% 5. The 5-year mortality exceeds that of colorectal cancer, breast cancer, stroke, acute myocardial infarction and prostate cancer 6…”
Section: Introductionmentioning
confidence: 99%